Architectural overreach; investigating the absence of structural engineers in building design: a case study in Herat, Afghanistan / Arif Alkozay, Amanollah Faqiri and Rahimullah Stankzai - Alkozay, Arif; Faqiri, Amanollah; Stankzai, Rahimullah (Universiti Teknologi MARA, Sarawak, 2024)
In the realm of architectural design and construction, collaboration between architects and structural engineers is fundamental for ensuring the safety, functionality, and aesthetic appeal of built environments. However, in regions like Afghanistan's Herat province, such collaboration is notably absent, with developers predominantly engaging solely with architects, sidelining the crucial role of structural engineers. This paper investigates the factors contributing to this lack of collaboration, focusing on developers' tendencies to exclude structural engineers from construction projects. Through a quantitative survey targeting developers and architects across Herat province, key drivers such as limited awareness, financial constraints, and seismic risk concerns were identified. The results reveal a concerning lack of awareness among respondents, with a majority indicating no prior knowledge of the role of structural engineers in building design. Additionally, a significant proportion of developers admitted to foregoing structural engineering scrutiny for most of their projects, highlighting a pervasive disregard for structural integrity. Financial considerations emerged as a predominant factor influencing developers' decisions, with cost cited as a primary reason for excluding structural engineers from construction projects. Furthermore, concerns about seismic risks, particularly earthquakes, were identified as another significant determinant. The findings underscore the urgent need for educational initiatives to enhance awareness about the importance of structural engineering and foster collaboration between architects and structural engineers. Addressing these factors is critical for mitigating risks associated with structural failure and ensuring the resilience of built environments in earthquake-prone regions like Herat province.